Sexual health clinic attendance and non-attendance in Britain: findings from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). (29th September 2017) - Tanton, Clare; Geary, Rebecca S; Clifton, Soazig; Field, Nigel; Heap, Katie L; Mapp, Fiona; Hughes, Gwenda; Johnson, Anne M; Cassell, Jackie A; Sonnenberg, Pam; Mercer, Catherine H
Abstract : Objectives: In Britain, sexual health clinics (SHCs) are the most common location for STI diagnosis but many people with STI risk behaviours do not attend. We estimate prevalence of SHC attendance and how this varies by sociodemographic and behavioural factors (including unsafe sex) and describe hypothetical service preferences for those reporting unsafe sex. Methods: Complex survey analyses of data from Britain's third National Survey of Sexual Attitudes and Lifestyles, a probability survey of 15 162 people aged 16–74 years, undertaken 2010–2012. Results: Overall, recent attendance (past year) was highest among those aged 16–24 years (16.6% men, 22.4% women), decreasing with age (<1.5% among those 45–74 years). Approximately 15% of sexually-active 16–74 year olds (n=1002 men; n=1253 women) reported 'unsafe sex' (condomless first sex with a new partner and/or ≥2 partners and no condom use, past year); >75% of these had not attended a SHC (past year). However, of non-attenders aged 16–44 years, 18.7% of men and 39.0% of women reported chlamydia testing (past year) with testing highest in women aged <25 years. Of those aged 16–44 years reporting unsafe sex, the majority who reported previous SHC attendance would seek STI care there, whereas the majority who had not would use general practice. Conclusion: While most reporting unsafe sex had not attended a SHC, many, particularly younger women, had tested for chlamydia suggesting engagement with sexual health services more broadly. Effective, diverse service provision is needed to engage those at-risk and ensure that they can attend services appropriate to their needs.